Phenolic compounds and antioxidant activity of blueberry cultivars grown in Brazil - Rodrigues,Eliseu (2011)
The aim of this study was to evaluate the content of the phenolic compounds and anthocyanins and the antioxidant activity of blueberry (Vaccinium sp.) cultivars grown in Brazil. The Folin-Ciocalteau method was applied in order to quantify the phenolic compounds and ABTS, DPPH, FRAP, and β-carotene/linoleic acid methods were applied in order to evaluated antioxidant activity. The phenolic compounds content ranged from 274.48 to 694.60 mg GAE.100 g-1 of fresh weight (FW). Anthocyanins content ranged from 40.62 to 378.31 mg.100 g-1 FW for Bluecrop and Tifblue cultivars, respectively. Antioxidant activities assessed by ABTS, DPPH and FRAP methods presented significant differences among the studied cultivars ranging from 1238.48 to 2445.96, 1014.24 to 2055.06 and 699.78 to 1740.25 µmol TEAC.100 g-1 FW, respectively. The results confirm the blueberry as a source of phenolic compounds with high antioxidant activity and also show that there are different levels of concentrations of phenolic compounds and antioxidant activity according to the cultivar and production location.